2013
DOI: 10.1016/j.ophtha.2012.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Applicants' Choice of an Ophthalmology Residency Program

Abstract: Objective To determine the factors most important to applicants when selecting an ophthalmology residency program. Design Cross-sectional survey. Participants All 595 applicants who submitted a rank list to the Ophthalmology Residency Matching Program for the 2012 match. Methods Participants anonymously completed a 25-item questionnaire after the submission of their rank lists. A multiple-choice format and ordinal scale were used to query applicants on demographics, career plans, and the importance of fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 13 publications
(11 reference statements)
4
56
0
Order By: Relevance
“…Applicants value the interaction with residents during an interview to assess resident morale, 28 esprit de corps, 29 and program ''red flags'' as perceived by applicants. 30 Ultimately, program directors and residents have reported that their ''gut feeling'' is important in creating their respective rank lists. 29,31 The resident selection interview also has been criticized for its ''dubious value,'' 32 due to the lack of a standardized approach and low interrater reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Applicants value the interaction with residents during an interview to assess resident morale, 28 esprit de corps, 29 and program ''red flags'' as perceived by applicants. 30 Ultimately, program directors and residents have reported that their ''gut feeling'' is important in creating their respective rank lists. 29,31 The resident selection interview also has been criticized for its ''dubious value,'' 32 due to the lack of a standardized approach and low interrater reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Although applicants generally consider academic factors of primary importance in residency selection, surveys from the last several years across many specialties have demonstrated that applicants also consider geography when deciding where they would like to go for residency. [3][4][5][6][7] One study noted that location is the third most-important ranking criterion among otolaryngology applicants, whereas program directors believe that location is a less-important factor. 3 The authors theorize that when selection committees have to decide between two equally qualified applicants, they are biased toward choosing the applicant that is closer geographically.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,8 Surgical volume was identified as a factor influencing rank order lists in a survey of ophthalmology residency applicants. 21 It is an integral part of training and can have implications on future career paths, yet 26% of programs provided surgical statistics. However, career placement of resident alumni may provide insight into career paths of residents training at an institution, and this was provided by about half of programs.…”
Section: Discussionmentioning
confidence: 99%